Termična analiza spontano kodranih polipropilenskih vlaken - Demšar, Andrej (Materiali in tehnologije, 2001)
This paper presents DSC (Differential Scanning Calorimetry) analyses of asymmetrically quenched PP filament yarns. The influence of the spinning temperature and the asymmetrical cooling on the melting temperature, the crystallinity and the shape of the melting curve was investigated. The research was showed that the highest melting temperatures are detected at the filament yarns spun from 220 to 260 oC, and that the crystallinity is reduced at higher spinning temperature. The DSC analyses also confirmed the prediction that with the asymmetrical cooling of the filament yarns in the spin shaft filament yarns with a bilateral supermolecular structure are formed. This means that the crimped polypropylene yarns consist of two different supermolecular structures, which are arranged in side-by-side order along the yarn.
Keywords: polipropilen; predenje iz taline; kodranje; teksturiranje; DSC analiza